2021
DOI: 10.1101/2021.05.11.443384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for cell-type specific evolution of viral fitness by SARS-CoV-2

Abstract: As the global burden of SARS-CoV-2 infections escalates, so does the evolution of viral variants which is of particular concern due to their potential for increased transmissibility and pathology. In addition to this entrenched variant diversity in circulation, RNA viruses can also display genetic diversity within single infected hosts with co-existing viral variants evolving differently in distinct cell types. The BriSΔ variant, originally identified as a viral subpopulation by passaging SARS-CoV-2 isolate hC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Here, three equilibrium 200 ns MD simulations were performed for the locked form of the unglycosylated and uncleaved ectodomain region of the D614G spike modelled from a wild-type model (17,20) based on the cryo-EM structure 6ZB5 (17) with and without LA bound (see Supplementary Material). In the original wild-type spike, D614 is located at the interface between monomers, with its sidechain directly interacting with residues across the subunit interface (55). RMSF profiles for the wild-type and D614G apo spikes are similar (Figure S15).…”
Section: Dynamic Response Of the D614g Spikementioning
confidence: 97%
See 1 more Smart Citation
“…Here, three equilibrium 200 ns MD simulations were performed for the locked form of the unglycosylated and uncleaved ectodomain region of the D614G spike modelled from a wild-type model (17,20) based on the cryo-EM structure 6ZB5 (17) with and without LA bound (see Supplementary Material). In the original wild-type spike, D614 is located at the interface between monomers, with its sidechain directly interacting with residues across the subunit interface (55). RMSF profiles for the wild-type and D614G apo spikes are similar (Figure S15).…”
Section: Dynamic Response Of the D614g Spikementioning
confidence: 97%
“…This site contains a polybasic PRRA insertion not found in other SARS-CoV-related coronaviruses (52). Cellbased assays show that deletion of the PRRA motif affects virus infectivity (19,(52)(53)(54)(55)(56). Note that in the simulations presented here, the furin site (located between R685 and S686) is not cleaved (see Supplementary Material).…”
Section: Fa Sites Modulate Key Motifs For Membrane Fusion or Antigenic Epitopes In The Spikementioning
confidence: 99%
“…Comparison with published fatty acid-protein structures suggested that the length and shape of the density agreed with linoleic acid (LA), an unsaturated C 18 fatty acid with two double bonds. Using hydrophobic interaction liquid chromatography-electrospray ionization mass spectrometry (HILIC-MS) and LC-MS-MS, the ligand in the RBD was confirmed to be LA (Toelzer et al, 2020;Gupta et al, 2022). Notably, only LA and no other fatty acids were identified by mass spectrometry (Toelzer et al, 2020).…”
Section: Cryo-em Of Sars-cov-2 Spike Glycoproteinmentioning
confidence: 99%
“…Deletion or mutation of the furin-cleavage site interferes with viral infection of lung cells and primary human airway epithelial cells (Peacock et al, 2021;Johnson et al, 2021). However, in patients infected with SARS-CoV-2, spikeprotein variants with a deleted furin-cleavage site have been identified as a subpopulation allowing the virus to infect other cell types, including epithelial cells (Peacock et al, 2021;Gupta et al, 2022;Pohl et al, 2021;Ogando et al, 2020;Sasaki et al, 2021;Klimstra et al, 2020). Interestingly, more recent SARS-CoV-2 variants of concern (VOCs) have acquired even more basic cleavage sites (HRRAR in Alpha and Omicron spike proteins and RRRAR in Delta spike proteins), resulting in a more complete cleavage at the furin site, contributing to the increased transmissibility of these VOCs (Wrobel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Structural studies have revealed that cleavage at the polybasic furin-cleavage site decreases the overall stability of SARS-CoV-2 Spike and facilitates the adoption of the open conformation that is required for Spike to bind the ACE2 receptor [27]. Consistent with this, deletion of the furin cleavage site in SARS-CoV-2 Spike promotes the adoption of closed form of the Spike and prevents cell-cell as well as virus-cell fusion in some cell types [16,26,28,29].…”
Section: Introductionmentioning
confidence: 88%